2016
DOI: 10.1016/j.egja.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between transdermal nicotine and melatonin patches on postoperative pain relief after laparoscopic cholecystectomy, a double-blind, placebo-controlled trial

Abstract: Background: This study evaluated the efficacy of transdermal nicotine (TDN) delivery system (15 mg/16 h) or transdermal melatonin (TDM) delivery system (7 mg) 2 h preoperatively for acute postoperative pain after laparoscopic cholecystectomy compared to placebo group (C). Methods: Sixty female non-smoker patients, aged 18-50 years and ASA I and II undergoing elective laparoscopic cholecystectomy under general anesthesia were included in this randomized controlled double-blind study. Patients were randomly divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The remaining 24 articles were assessed according to RoB2, and 7 of them were excluded due to the papers not presenting the outcomes clearly or being assessed as low in quality. In this systematic review with meta-analysis, a total of 17 studies were found to be eligible, including 5 studies of pain tolerance (n = 210), 5 studies of pain threshold (n = 210), and 12 studies of pain scores (n = 1249) [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The descriptive information and risk of bias assessment for each of these 17 trials are presented in Table 1.…”
Section: Study Selection and Characteristics Of The Study Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 24 articles were assessed according to RoB2, and 7 of them were excluded due to the papers not presenting the outcomes clearly or being assessed as low in quality. In this systematic review with meta-analysis, a total of 17 studies were found to be eligible, including 5 studies of pain tolerance (n = 210), 5 studies of pain threshold (n = 210), and 12 studies of pain scores (n = 1249) [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The descriptive information and risk of bias assessment for each of these 17 trials are presented in Table 1.…”
Section: Study Selection and Characteristics Of The Study Samplesmentioning
confidence: 99%
“…For instance, five clinical studies involving laboratory-induced pain found that short-term application increased pain thresholds and pain tolerance to cold percussion tests in healthy volunteers [10][11][12][13][14]. Three clinical studies documented the effectiveness of both nicotine patches and nicotine nasal sprays in alleviating postoperative pain [8,15,16]. In contrast, six clinical studies revealed that the anti-nociceptive effect of nicotine patches and nicotine nasal spray on postoperative pain was less apparent [9,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The included trials were published between 2006 and 2019, and they involved a total of 1967 participants (983 in an intervention group and 984 in a control group). Out of 30 trials, 12 trials investigated acute postoperative pain after the surgery under general anesthesia [12][13][14][15][18][19][20]24,26,30,36,40], four trials did acute postoperative pain after the surgery under local and epidural anesthesia [15,25,28,29], four trials investigated acute procedural pain [23,27,32,33], and five trials investigated chronic pain [17,21,35,37,38]. The duration of pain was not reported in the remaining five trials [11,22,31,34,39].…”
Section: General Characteristics Of Trialsmentioning
confidence: 99%
“…The duration of pain was not reported in the remaining five trials [11,22,31,34,39]. In the methodological quality score assessed by the Cochrane Risk of Bias Tool, the average number of low risk of bias was 5.8, and 19 trials demonstrated low risk of bias in 6 items or more and were considered to be high quality [14,16,[18][19][20][21][22]24,28,29,[31][32][33][34][35][36][37][38][39], while the remaining 11 trials demonstrated a low risk of bias in 5 items or less [11][12][13]15,17,23,[25][26][27]30,40] (Table 2).…”
Section: General Characteristics Of Trialsmentioning
confidence: 99%
See 1 more Smart Citation